2021
DOI: 10.1111/anec.12894
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of clinical applications of interlead ECG heterogeneity assessment: From myocardial ischemia detection to sudden cardiac death risk stratification

Abstract: Heterogeneity in depolarization and repolarization among regions of cardiac cells has long been recognized as a major factor in cardiac arrhythmogenesis. This fundamental principle has motivated development of noninvasive techniques for quantification of heterogeneity using the surface electrocardiogram (ECG). The initial approaches focused on interval analysis such as interlead QT dispersion and Tpeak–Tend difference. However, because of inherent difficulties in measuring the termination point of the T wave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…ECG features have been used to diagnose or predict cardiovascular events. For instance, heterogeneity of R-wave and T-wave morphology and ST-segment elevation have been used to diagnose ventricular arrhythmias ( 25 , 26 ). ST-segment elevation myocardial infarction (STEMI) has also been used for chronic HF prediction ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…ECG features have been used to diagnose or predict cardiovascular events. For instance, heterogeneity of R-wave and T-wave morphology and ST-segment elevation have been used to diagnose ventricular arrhythmias ( 25 , 26 ). ST-segment elevation myocardial infarction (STEMI) has also been used for chronic HF prediction ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of TWA also predicted the occurrence of nonsustained ventricular tachycardia during PCI in post‐MI patients (Takasugi et al, 2011; Verrier et al, 2013). In the Finnish Health Survey 2000, TWH analyzed from resting 12‐lead ECGs identified subjects who died suddenly with 2.8 (1.8‐4.5) hazard ratios ( p < .001) (Kenttä et al, 2016; Verrier & Huikuri, 2017; Verrier et al, 2021). The results of the ATRAMI study also demonstrated the predictive capacity of altered autonomic tone (HRV) and baroreceptor reflex sensitivity (BRS) in post‐MI patients (La Rovere et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This analytical approach was used to calculate TWH from 12‐lead ECG recordings at rest, as described in detail (Nearing & Verrier, 2003; Verrier et al, 2021; Verrier & Huikuri, 2017). Basically, the approach superimposes simultaneous waveforms from three precordial leads, typically V 4 , V 5 , and V 6 , and calculates the variance or splay about the mean waveform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrocardiograms (ECG), Doppler ultrasounds, arteriography, computed tomography (CT), and other imaging techniques, among others, are commonly used in clinical settings to evaluate cardiovascular disease (CVD), all of which are able to identify the disease accurately [7][8][9]. In addition, patients who have arrhythmia and myocardial ischemia are required to have real-time electrocardiogram monitoring [10]. Conventional cardiovascular monitoring, on the other hand, frequently has its limitations due to the paucity of medical resources, which can be inconvenient, as well as the utilization of cumbersome and pricey technology for episodic diagnosis in hospital settings.…”
Section: Introductionmentioning
confidence: 99%